The Role of Terraced Paddy Fields and Its Critical Issues in Sustaining a Mountainous Tropical Monsoon Rural Community: Case Study of Malasari Village, Bogor Regency, Indonesia - Kenta Tsuchiya; Ernan Rustiadi; Darmawan; Shinya Funakawa (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2021)
Terraced paddy fields play an important role not only in the food production function, but also in flooding control, water source recharge, and soil erosion and landslide prevention in mountainous area. Abandonment has been occurring in many countries due to natural condition climate, low-productive, less economic condition, depopulation, aging, and poor work efficiency. However, the terraced fields in Malasari village, Bogor Regency are relatively sustained and constantly maintained by traditional local farmers. Therefore, this study aims to seek keys to how to maintain of the terraced paddy fields by local farmers in Malasari village. The survey was conducted from October 2019 to January 2020 on Malasari village (6°40’S and 106°31’E) by using primary and secondary data with a sample of 28 households. Questionnaire survey was conducted to elicit primary data on farmer’s basic information. Verification of land cover in Malasari village was carried out by visual interpretation land cover in images obtained from drone image in 2019. The terraced paddy fields have been maintained by local farmers contentiously. Two factors are discovered maintained the terraced paddy fields, namely: (1) the local wisdom technique is an act that has direct influences on the physical structure of terraced paddy fields for maintaining, especially land management which is plowing and making levee are playing an important role, and (2) social capital is an act that has indirect influences on the terraced paddy fields. These factors interact with each other to maintain the terraced paddy fields.